Safety and usability of oncology information systems – a systematic review - Cihoric, Nikola; Riggenbach, Elena; Putora, Paul Martin; Dennstädt, Fabio (Frontiers in Oncology, 2024)
BackgroundDigitalization has become integral to healthcare and specifically cancer treatment. Healthcare providers in oncology widely use electronic data collection and management systems in contemporary clinical practice. However, some reports point to severe problems regarding usability, which negatively impact the clinical workforce, as well as safety issues related to electronic health records, which potentially endanger patients. This systematic review aims to evaluate current scientific literature on the usability and safety aspects of electronic health records in oncology.MethodsWe conducted a systematic literature review on PubMed and Scopus to identify articles on the usability and safety aspects of electronic health records and clinical information systems utilized in oncological care. Two authors independently evaluated available literature according to predefined inclusion and exclusion criteria. Finally, we quantitatively analyzed and classified the reported findings.ResultsOur literature research strategy retrieved 1032 articles. We included seven articles for further processing. Three projects focused on the assessment of electronic health record functionality, three projects described the process of user-driven design, and one article described remediation procedures introduced to compensate inability of computer systems to adapt to user requirements.ConclusionLiterature on the usability and safety of electronic health records in oncology is sparse. It is essential to raise awareness and start systematic activity to promote research on the usability of electronic health records in oncology.